Prevalence of previously diagnosed diabetes mellitus in Mexico - Rosalba Rojas-Martínez; Ana Basto-Abreu; Carlos A Aguilar-Salinas; Emiliano Zárate-Rojas; Salvador Villalpando; Tonatiuh Barrientos-Gutiérrez (Instituto Nacional de Salud Pública, 2018)
Objective. To compare the prevalence of previously diagnosed diabetes in 2016 with previous national surveys and to describe treatment and its complications. Materials and methods. Mexico's national surveys Ensa 2000, Ensanut 2006, 2012 and 2016 were used. For 2016, logistic regression models and measures of central tendency and dispersion were obtained. Results. The prevalence of previously diagnosed diabetes in 2016 was 9.4%. The increase of 2.2% relative to 2012 was not significant and only observed in patients older than 60 years. While preventive measures have increased, the access to medical treatment and lifestyle has not changed. The treatment has been modified, with an increase in insulin and decrease in hypoglycaemic agents. Conclusions. Population aging, lack of screening actions and the increase in diabetes complications will lead to an increase on the burden of disease. Policy measures targeting primary and secondary prevention of diabetes are crucial.